Revista SATHIRI: Sembrador Vol. 15, N° 2 _Completa - Comisión de Publicaciones, (SATHIRI, 2021)
SATHIRI volume 15, number 2 - period July – december 2020. Semiannual magazine of the Politécnica Estatal del Carchi University that aims to disseminate the research results of the institution as well as other national and international universities. UPEC's research areas are: Foreign Trade and Customs; Logistics and Transportation Management; Commercial Negotiation and Marketing; Business Development and Innovation; Public administration; Promotion and Development of Tourist Heritage; Development of Agricultural and Agro industrial Production; Management and Conservation of Natural Resources; Foods; Computer's science; Integral Health; Education; and Border Problems. It is also multidisciplinary and involves all results and advancement of human knowledge under the formats of scientific papers, reflective and speculative articles, states art or research advances whose ideas are expressed exclusively under the responsibility of the authors. Articles can only be reproduced citing the source